A gas turbine combustion chamber modeling by physical model - Glavan, Ivica, inženjer strojarstva (Array, 2021)
The validity of the gas turbine unit model largely depends on the accuracy of the flue gas temperature value calculation at the gas turbine inlet (TIT). This temperature is determined by the maximum combustion temperature. In variable running mode, the temperature value is regulated by changing the ratio of air and fuel at the inlet to the combustion chamber. The paper presents a model of a gas turbine combustion chamber using Modelica, an object-oriented language for modeling complex physical systems with the aim of determining the temperature of combustion flue gases, specific heat capacity, enthalpy, and flue gas composition at different gas turbine loads.